Geometrical product specifications (GPS). Dimensional and geometrical tolerances for moulded parts. General dimensional and geometrical tolerances and machining allowances for castings using ± tolerances for indicated dimensions Part 3, (1st March 2023) - British Standards Institution,
No abstract available